2021
DOI: 10.1038/s41419-020-03337-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93/STAT3 signalling pathway mediates retinal microglial activation and protects retinal ganglion cells in an acute ocular hypertension model

Abstract: Glaucoma is a common neurodegenerative disease and a leading cause of irreversible blindness worldwide. Retinal microglia-mediated neuroinflammation is involved in the process of optic nerve damage, but the mechanisms driving this microglial activation remain mostly elusive. Previous investigations reported that microRNAs are associated with the retinal microglial reaction and neural apoptosis. In the present study, we found that microRNA-93-5p (miR-93) played a key role in the reaction of retinal microglial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
(58 reference statements)
2
12
0
Order By: Relevance
“…1D). Similar findings were also showed in mice IR injury, a well-validated model of glaucoma [27,28] (Fig. 1D).…”
Section: Altered Tryptophan Metabolism and Ahr Signaling Was Found In...supporting
confidence: 86%
See 1 more Smart Citation
“…1D). Similar findings were also showed in mice IR injury, a well-validated model of glaucoma [27,28] (Fig. 1D).…”
Section: Altered Tryptophan Metabolism and Ahr Signaling Was Found In...supporting
confidence: 86%
“…Here, we postulated a new perspective of supplementing endogenous tryptophan derived AhR ligands to confer neuroprotection in glaucoma. We aimed to modulate the intrinsic changes of tryptophan metabolism and AhR signaling that affect microglia activity to inhibit local inflammation in glaucoma [ 28 , 41 ]. Previous study discussed the role of tryptophan metabolism in POAG, mainly focusing on the association of microglia mediated neurotoxicity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fuchs et al ( 30 ) reported the ability of miRNA-93 to suppress TGFβ-induced VEGFA secretion from retinal pigment epithelium cell lines and to convert TGFβ-induced mesenchymal retinal epithelial cells back to the epithelial-like status, which part-explains our finding of a gradual decrease in miRNA-93 expression across patient groups, with the lowest expression level in patients with proliferative diabetic retinopathy. Similarly, miR-93 expression was reduced in acute ocular hypertension retinae compared to controls and miR-93 upregulation suppressed microglial proliferation, inflammation, and cytokine secretion ( 31 ). Moreover, miR-93 was also investigated in diabetic renal vascular complications suggesting its antiangiogenic and antifibrotic properties and showed decreased expression in renal tissue of patients with diabetic nephropathy ( 32 ), and in a diabetic kidney model was speculated to affect nucleosome remodeling ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin can inhibit microglia activation through the PI3K/Akt/Stat3/NF-κB signal axis and protect pericytes from apoptosis ( Tang L. et al, 2022 ). And MicroRNA-93-5p can restrain M1 microglia activation by silencing STAT3 ( Wang et al, 2021 ).…”
Section: Effect Of Microglia On Retinal Vasculature and Brb In Variou...mentioning
confidence: 99%